The Effect Of N Fertilizer And Vermicompost Fertilizer On The Growth And Yield Of Sweet Corn (Zea mays saccharata Sturt) Cultivar Exsotic Pertiwi F1 - Muhammad Aji Abadillah; Khoirul Al Farisi; Mukhammad Fariz Ismail; Wijaya Wijaya (Ann Publisher, 2025)
The purpose of this study is to ascertain how sweet corn growth and yield are impacted by urea and vermicompost fertilizer dosages. From June to August 2024, the study was carried out at Mekar Jaya Village, Gantar District, Indramayu Regency, utilizing a randomized block design (RBD) consisting of 9 treatments of nitrogen fertilizer and vermicompost fertilizer with three replicates. The urea doses were 100, 200, and 300 kg/ha, and the vermicompost doses were 5, 10, and 15 tons/ha, resulting in 27 experimental plots. The variables observed included plant height, number of leaves, diameter of cobs, length of cobs, root volume, nitrogen uptake, weight of cobs per plant, and weight of cobs per plot. The data were analyzed using the F test and DMRT at the 5% level. The growth and yield of sweet corn (Zea mays saccharata Sturt) were greatly influenced by the dosage of nitrogen fertilizer (urea) and vermicompost applied. Significant differences were found in various variables, such as plant height, number of leaves, stem diameter, root volume, cob diameter, cob length, cob weight per plant, and cob weight per plot. For the glucose content variable, there were no significant differences. In treatment I, the combination of 300 kg/ha of urea and 15 tons/ha of manure yielded the best results for most growth and yield variables.